Improving Public Services: Development of Drinking Water Supply System in West Halmahera - Nditi S Baranyanan; Mochammad Rozikin; Ainul Hayat (University of Merdeka Malang, 2024)
To improve public services, this study will explain and assess the development of a drinking water supply system (SPAM) at the Public Works and Spatial Planning Office (PUPR) of West Halmahera Regency. It will also examine the elements that facilitate and impede the development of SPAM. The purpose of this study is to meet the Minimum Service Standards (SPM) at the PUPR Office of West Halmahera Regency by enhancing the quality of public services in the area of drinking water through SPAM. Consequently, the author used qualitative descriptive research methodologies and cited legislation concerning the Development of Drinking Water Supply Systems (SPAM). These findings show that improving public services, especially the development of drinking water supply systems, is an important aspect of ensuring access to safe and clean drinking water for people in West Halmahera Regency. The improvement of the system involves various factors, Physical Aspects (Technical Aspects), Non-Physical Aspects (Institutional Aspects, Management Aspects, Financial Aspects, Community Role Aspects, and Legal Aspects) as stated in Government Regulation No. 16 of 2005, concerning the Development of Drinking Water Supply Systems. For example, Besharov et al. stressed the importance of improving public services, which is in line with achieving universal and equitable access to drinking water services as part of the Sustainable Development Goals (SDGs).